Climate change transforms the functional identity of Mediterranean coralligenous assemblages. (16th March 2021) - Gómez‐Gras, Daniel; Linares, Cristina; Dornelas, Maria; Madin, Joshua S.; Brambilla, Viviana; Ledoux, Jean‐Baptiste; López‐Sendino, Paula; Bensoussan, Nathaniel; Garrabou, Joaquim
Abstract: Quantifying changes in functional community structure driven by disturbance is critical to anticipate potential shifts in ecosystem functioning. However, how marine heatwaves (MHWs) affect the functional structure of temperate coral‐dominated communities is poorly understood. Here, we used five long‐term (> 10 years) records of Mediterranean coralligenous assemblages in a multi‐taxa, trait‐based analysis to investigate MHW‐driven changes in functional structure. We show that, despite stability in functional richness (i.e. the range of species functional traits), MHW‐impacted assemblages experienced long‐term directional changes in functional identity (i.e. their dominant trait values). Declining traits included large sizes, long lifespans, arborescent morphologies, filter‐feeding strategies or calcified skeletons. These traits, which were mostly supported by few sensitive and irreplaceable species from a single functional group (habitat‐forming octocorals), disproportionally influence certain ecosystem functions (e.g. 3D‐habitat provision). Hence, MHWs are leading to assemblages that are deficient in key functional traits, with likely consequences for the ecosystem functioning. Abstract : Marine heatwaves (MHWs) are altering the structure of temperate coral‐dominated communities worlwide. Yet, the long‐term consequences for ecosystem functioning remain mostly uknown. Here, we quantified changes in functional structure of Mediterranean coralligenous assemblages by conducting a mulit‐taxa, trait‐based analysis. Our results show that MHWs are leading to assemblages that are deficient in key functional traits, with likely consequences for the ecosystem functioning.